Strengthening the Existence of “Kacang Rendang” MSMEs in Nagari Tigo Balai through Packaging Design Assistance - Yanti, Delvi; Puari, Aninda Tifani; Mailani, Fitri; Permata, Deivy Andhika (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2025)
Peanuts are one of the leading commodities of Nagari Tigo Balai, Matur District, Agam Regency, West Sumatra. Some people in Nagari Tigo Balai have processed peanuts into rendang peanuts and many still sell their raw peanuts directly from their harvest. The processed peanuts from Nagari Tigo Balai craftsmen are still packaged in ordinary packaging, namely using transparent plastic and makeshift labels. This activity aims to provide assistance to the peanut MSMEs of Nagari Tigo Balai to produce packaging according to the target market. This activity is carried out in several stages, namely socialization, packaging design, and assistance in the use of packaging. One of the productive peanut MSMEs in Nagari Tigo Balai is the LBM MSMEs. The assistance activity has produced three packaging designs, namely the PP standing pouch packaging design, the PP plastic packaging sticker label design, and the PP plastic packaging screen printing label design. The most suitable and needed packaging design for the rending peanut craftsmen of LBM MSME Nagari Tigo Balai is the sticker label on PP plastic packaging. The chosen design is consistent with the target market of rendang peanuts produced by LBM MSME Nagari Tigo Balai, which includes consignment system at souvenir outlets, direct sales in nearby markets, and distribution through local traders.